Perancangan Sistem Instrumentasi Pada BIOPARKS Biometric Parking System Menggunakan Mikrokontroler Wemos D1R1 - Siti Robiah Adawiah; Rahmat Hidayat; Ulinnuha Latifa (LPPM Poltek ST Paul, 2021)
Parking lots are a public means of storing vehicles but the high crime rate of vehicle theft makes vehicle owners feel insecure when leaving their vehicles while doing activities outside the home. To solve this problem, a systematic parking security system using a biometric system was created. The biometric system is a security system that can identify a person's characteristics by using Wemos as a microcontroller to process the input from the sensor then produce output to the actuator and send data to the BYLNK application. This research was conducted to design an instrumentation system so that the system implemented can work properly. The final results obtained are the characteristics of each sensor and actuator used, including a fingerprint sensor with an error value of 0.8%, an ultrasonic sensor with a sensitivity value of 1.1156 cm with an accuracy value of 99.83%, an error value of 0, 16% and servo motors with an error value of 0.15%.